2021
DOI: 10.1001/jamasurg.2020.5672
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Plating vs Closed Reduction for Fractures in the Distal Radius in Older Patients

Abstract: IMPORTANCEThe burden of injury and costs of wrist fractures are substantial. Surgical treatment became popular without strong supporting evidence.OBJECTIVE To assess whether current surgical treatment for displaced distal radius fractures provided better patient-reported wrist pain and function than nonsurgical treatment in patients 60 years and older. DESIGN, SETTING, AND PARTICIPANTSIn this multicenter randomized clinical trial and parallel observational study, 300 eligible patients were screened from 19 cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 49 publications
(116 reference statements)
0
61
2
Order By: Relevance
“…Randomized trials similar to ours comparing non-operative treatment with volar locking plates in elderly patients have been carried out in the last decade but few studies present data beyond 1 year of follow-up. In contrast to our findings, most authors do not report any significant benefit of surgical treatment [ 9 , 20 , 22 , 23 , 25 ]. The inclusion criteria however differ between studies in both age range and degree of fracture displacement, making comparisons complicated.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Randomized trials similar to ours comparing non-operative treatment with volar locking plates in elderly patients have been carried out in the last decade but few studies present data beyond 1 year of follow-up. In contrast to our findings, most authors do not report any significant benefit of surgical treatment [ 9 , 20 , 22 , 23 , 25 ]. The inclusion criteria however differ between studies in both age range and degree of fracture displacement, making comparisons complicated.…”
Section: Discussioncontrasting
confidence: 99%
“…Arora et al present no differences between groups at 12 months, but the fractures in their study healed in nearly anatomical positions, even in the non-operative group [ 20 ]. Lawson et al showed no benefit as measured in PRWE in the RCT with patients > 60 years including fractures with more than 10-degrees of dorsal displacement [ 22 ]. At 12-months follow-up Egol et al did not find surgery to be superior according to DASH, in a case control study of patients aged > 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the functional recovery and complication rate were not compromised in this group. Additionally, in this group there is a growing body of evidence in support of non-operative treatment in the long-term and a suggestion to reserve surgery for patients in need of fast recovery [ 15 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 Multiple trials and studies have also demonstrated nonsurgical treatment of distal radius fractures to be equivocal to surgical treatment. 3 , 5 , 7 , 13 , 22 For patients considering percutaneous operative intervention as opposed to traditional fixation with a volar locking plate, percutaneous pinning of unstable extra-articular fractures of distal radius shows marginal improvement in radiological outcomes compared to cast alone. Despite this, there was no difference in functional outcomes.…”
Section: Methodsmentioning
confidence: 99%